Parkinson's disease effect on autonomic modulation: an analysis using geometric indices - Mileide Cristina Stoco-Oliveira; Ana Laura Ricci-Vitor; Laís Manata Vanzella; Heloisa Balotari Valente; Vitor Eduardo dos Santos Silva; Larissa Borba André; Augusto Cesinando de Carvalho; David Matthew Garner; Luiz Carlos Marques Vanderlei (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: Parkinson's disease (PD) produces autonomic changes, indicating lower parasympathetic modulation and global variability, but these changes need further studying regarding geometric methods. Objective: To investigate the autonomic modulation in individuals with PD using heart rate variability (HRV) indices obtained through geometric methods. Methods: This is a cross-sectional study that assessed 50 individuals, split into two groups: PD group (PDG; n=26; 75.36±5.21 years) and control group (CG; n=24; 75.36±5.21 years). We evaluated the autonomic modulation by measuring the heart rate beat-to-beat for 30 min with the individual in supine rest using a heart rate monitor and assessed geometric indices (RRtri, TINN, SD1, SD2, SD1/SD2 ratio, and qualitative analysis of the Poincaré plot). Results: Significant reductions were found in RRtri, TINN, SD1, and SD2 indices among PDG compared to CG. Regarding the SD1/SD2 ratio, no significant changes were detected between the groups. The Poincaré plot demonstrated that individuals with PD had lower beat-to-beat dispersion in RR intervals, in addition to greater long-term dispersion of RR intervals compared to CG. Conclusions: The results suggest a reduction in the parasympathetic autonomic modulation and global variability in individuals with PD compared to controls, regardless of sex, age, and body mass index.